2016
DOI: 10.1634/theoncologist.2015-0319
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Olaparib (AZD-2281) After Standard Systemic Therapies for Disseminated Colorectal Cancer

Abstract: Background. Effective new agents for patients with colorectal cancer (CRC) with disease progression during standard therapy regimens are needed. We hypothesized that poly ADP ribose polymerase (PARP) inhibitor therapy in patients with CRC and inefficient tumor DNA repair mechanisms, such as those with high-level microsatellite instability (MSI-H), would result in synthetic lethality. Methods.This was an open-label phase II trial testing olaparib 400 mg p.o. b.i.d. for patients with disseminated, measurable CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 33 publications
(30 reference statements)
0
50
0
Order By: Relevance
“…More recently, a phase II clinical trial investigated off‐label of use of PARPi in MSS and MSI CRCs to determine whether microsatellite status was a predictive marker of PARPi response. The results of this study suggested that PARPi alone did not affect patient outcomes regardless of microsatellite status (Leichman et al ., ). While PARPi have been approved for the treatment of other cancer types that exhibit HR deficiency, PARPi are not currently used for CRC patients.…”
Section: Targeting Dna Repair In Colorectal Cancermentioning
confidence: 99%
“…More recently, a phase II clinical trial investigated off‐label of use of PARPi in MSS and MSI CRCs to determine whether microsatellite status was a predictive marker of PARPi response. The results of this study suggested that PARPi alone did not affect patient outcomes regardless of microsatellite status (Leichman et al ., ). While PARPi have been approved for the treatment of other cancer types that exhibit HR deficiency, PARPi are not currently used for CRC patients.…”
Section: Targeting Dna Repair In Colorectal Cancermentioning
confidence: 99%
“…This approach has been investigated using poly(ADP)ribose polymerase (PARP) inhibitors in BRCA gene‐mutated ovarian and breast cancers [20], [21]. A phase II study with the PARP inhibitor olaparib did not demonstrate activity in advanced CRC patients with MSS or MSI‐high tumors [22]. Nonetheless, POLE ‐deficient cancers encompass a different mechanism of failed DNA repair, and targeted therapies such as these may prove successful in the future.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%
“…In the BRCA wild‐type HRD subgroup, HRD status was determined based on the dichotomized HRD score (n = 106) or HRD‐LOH (genomic loss of heterozygosity) score (n = 188) using a predefined threshold. Mutations in HRD genes rather than BRCA1/2 included ATM low or negative (n = 125), high‐level microsatellite instability (n = 13), PTEN loss (n = 30), and other aberrations in DNA repair genes (n = 16) . Patients with BRCA wild‐type, low HRD or HRD‐LOH score, ATM high or positive, or microsatellite‐stable or without defects in DNA repair gene were collectively classified as the non‐HRD subgroup (n = 1,417).…”
Section: Resultsmentioning
confidence: 99%
“…However, they support the hypothesis that patient stratification based on underlying genetic defects in DNA repair pathways could be a meaningful approach for identifying patient populations that are likely responding to PARPis. To date, the clinical results of tumor response and prognosis in different HRD cancer populations appear to be inconsistent . In terms of long‐term clinical benefit, such as progression‐free survival (PFS) and overall survival (OS), the precise role of HRD as a predictive biomarker has not been well established.…”
Section: Introductionmentioning
confidence: 99%